A comparison of two Detailed Clinical Model representations: FHIR and CDA - Smits, Marten; Kramer, Ewout; Harthoorn, Martijn; Cornet, Ronald (European Journal for Biomedical Informatics, 2015)
Introduction:In recent years several standardized modeling methods have been proposed that separate health related data models from their underlying technical data model. These methods presuppose representation of information independently of (or uninfluenced by) technical considerations. Among these methods is the Detailed Clinical Model (DCM) paradigm. One of the pillars of this paradigm is that all representations convey the same meaning and are independent of the technical standard that is used and the DCM standard claims to achieve that. In this paper we will challenge that claim by modeling the specific DCMs in two different technical standards (CDA and FHIR) and testing if messages based on these models are interconvertible. Methods: We identified and categorized the problems that may arise when mapping or combining multiple standards creating representations of selected DCMs in both FHIR and CDA to determine possible fundamental problems using a technology independent model (DCM) to represent technical models (FHIR and CDA). To test if the theoretical problems we encountered while creating our example messages also occur during the actual transformation, and to determine any additional problems, we attempted to transform the Clinical Document Architecture (CDA) representations of the DCMs to the FHIR representations using Extensible Style sheet Language Transformations (XSLT). Results: Most aspects of the DCMs could be properly represented in both FHIR and CDA, and can be transformed from CDA to FHIR. However, we identified fundamental issues where information was lost or its meaning was changed. This results in fundamental difficulties during the implementation of the standards and when transforming one standard to another. Conclusion: Our research shows that possible loss and change of meaning and lack of interconvertibility occurs when implementing two separate technical standards based on the same DCMs. This indicates that it does matter which technical standard is used to implement a DCM.
Keywords: zpracování přirozeného jazyka; chorobopisy - spojování; elektronické zdravotní záznamy; Natural Language Processing; systémová integrace; šíření informací; Models, Theoretical; Medical Informatics; Health Information Management; teoretické modely; Systems Integration; Information Dissemination; Electronic Health Records; řízení zdravotnických informací; lékařská informatika; Medical Record Linkage